(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The CFD transient simulation of superheating the refrigerant R410 through the heat exchange with the evacuated tube water heating system of the hybrid split air conditioner that is subjected to solar radiation of constant intensity with the contribution of fan accelerated air is performed by the ANSYS-CFX code. The comparison with experimental work showed a minimum percentage error 8% of the predicted refrigerant evaporative heat transfer with storage tank horizontal tubing. In addition, the results denoted high absorption rate for the evacuated tubes, reducing highly reversed heat transmission for the circulated water.